Multivariate statistical applied to data costs post-harvest coffee - Santos, Rafael Vargas; Vieira, Henrique Duarte; Borém, Flávio Meira; Prado, Mariele Vilela Bernardes (Coffee Science - ISSN 1984-3909, 2017)
The choice of method of processing coffee is decisive on the profitability of the coffee activity, and will depend on several factors. Thus, due to the existence of many variables is common producer to question the viability of certain types of processing. Thus, the objective in this research was carried out a study of the major influencing factors on the cost of post-harvest coffee. Forty-six farms in the regions of the Cerrado, Matas de Minas and southern Minas Gerais State answered a questionnaire in order to enable this analysis. The application of multivariate techniques of cluster analysis, factor analysis and principal component analysis, allowed us to conclude that farms with higher costs simulated were those with the highest percentages of wet coffee production.